Menstrual migraine. Diagnosis, pathogenesis and review of acute and short-term prevention pharmacotherapy - Furtak, Daria; Grela, Wiktor; Niewiadomska, Jagoda; Tulej, Dawid; Głogowska, Paulina; Dziedzic, Alicja; Gniaź, Natalia; Marciniuk, Dominika; Marko, Natalia; Górska, Aleksandra (Journal of Education, Health and Sport, 2024)
Background Menstrual migraine describes migraines that occur in alignment with the menstrual cycle, affecting women of diverse age ranges. This condition is relatively common, presenting a unique challenge due to the heightened intensity of pain during these attacks. Additionally, these migraines are often more resistant to standard treatment methods, underscoring the need for specialized approaches to management and relief. Methods Review of double-blind, placebo-controlled cohort studies found using PubMed, Google Scholar and Cochrane. Results Triptans are considered a primary treatment option for managing acute menstrual migraine episodes, with their effectiveness being the most extensively researched among available therapies. Recently, lasmiditan has emerged as a newer medication showing promising potential for this specific application as well, adding to the options available for menstrual migraine relief. Furthermore, triptans have been validated as effective in the short-term prevention of migraine. The most recent pharmacological advancements that have demonstrated efficacy for this condition are monoclonal antibodies which target the CGRP receptor: Erenumab and Galcanezumab. Conclusion There are effective approaches to both treating and preventing acute migraine attacks. However, menstrual migraine is a condition that requires greater awareness and recognition, as this would allow for the improved and more effective use of existing medications and treatments.